A Healable, Semitransparent Silver Nanowire‐Polymer Composite Conductor. (24th June 2013) - Gong, Chaokun; Liang, Jiajie; Hu, Wei; Niu, Xiaofan; Ma, Sungwon; Hahn, H. Thomas; Pei, Qibing
<x xml:space="preserve">Abstract</x> A quick recovery: A semitransparent composite conductor comprising a layer of silver nanowire percolation network inlaid in the surface layer of a Diels–Alder‐based healable polymer film is fabricated. The composite is flexible and highly conductive, and is capable of both structural and electrical healing via heating. Cut samples that completely lose their conductivity can recover 97% of it within 5 minutes of heating at 110 °C. The cutting and healing can be repeated at the same location for multiple cycles. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>